THE RELATIONSHIP BETWEEN KNOWLEDGE AND THE ATTITUDE OF PROSPECTIVE BRIDES AND GROOMS TOWARD PREMARITAL SCREENING - SAMPARA, RISDAYANTI; Endyka Erye Frety; Amalia, Rize Budi (Badan Kependudukan Dan Keluarga Berencana Nasional, 2024)
Healthy pregnancy planning through premarital screening aims to reduce high-risk pregnancies with early intervention in prospective brides. However, it is less popular among prospective brides, a total of 74.4% of prospective brides do not know the benefits of premarital screening, this can affect the assessment of prospective brides on premarital screening even though premarital screening services are required by the government. This study aims to analyze the relationship between knowledge and the attitude of prospective brides regarding premarital screening. Method study is quantitative research with an observational analytical design, a cross-sectional study approach conducted on 63 samples with consecutive sampling techniques. The measurement of knowledge level and attitude uses a questionnaire and the Fisher Exact Statistics test. This study shows that the knowledge of prospective brides about premarital screening is mostly in the category of less than 44.4% and the majority attitude is positive 81%. There was a significant correlation (p < 0.001) between knowledge and attitudes towards premarital screening. It can be concluded that knowledge can affect the attitude and assessment of the prospective brides and groom towards premarital screening. Therefore, strategic steps are needed such as the integration of education in premarital counseling, the development of community-based campaigns.